2021
DOI: 10.1186/s13046-021-01917-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived organoids and high grade serous ovarian cancer: from disease modeling to personalized medicine

Abstract: Background High grade serous ovarian cancer (HGSOC) is among the deadliest human cancers and its prognosis remains extremely poor. Tumor heterogeneity and rapid acquisition of resistance to conventional chemotherapeutic approaches strongly contribute to poor outcome of patients. The clinical landscape of HGSOC has been radically transformed since the advent of targeted therapies in the last decade. Nevertheless, the lack of predictive biomarkers informing on the differential clinical benefit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Other recent reviews have examined the use of PDOs in EOC (54,55). A total of two studies focused on EOC, also included in the present review (27,47).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent reviews have examined the use of PDOs in EOC (54,55). A total of two studies focused on EOC, also included in the present review (27,47).…”
Section: Discussionmentioning
confidence: 99%
“…However, another trial (NCT00499499) revealed that two patients experienced vision loss [ 68 ]. More recently, an ex vivo longitudinal observational phase II trial (NCT04555473) was started to evaluate the reliability of high grade serous ovarian carcinoma (HGSOC) organoids as a model for the patients’ response to treatments [ 95 ]. The rationale for this study is based on MYC amplification in HGSOC (TCGA Firehouse Legacy), which could possibly expose these tumors to vulnerability to splicing inhibition.…”
Section: Splicing-based Therapeutic Strategiesmentioning
confidence: 99%
“…Subsequently, these organoids were genetically manipulated for drug screening applications [ 112 ]. In summary, ovarian cancer organoids maintain the gene expression pattern of their tumor of origin and can be used to target genes and guide future research on targeted therapy [ 113 ]. Ovarian cancer organoids can also be cultured on a large scale to enable high‐throughput drug screening.…”
Section: Applications Of Organoids In Various Types Of Cancermentioning
confidence: 99%